Art, a way for healing - Meza Alvarez, Milagros (2010)
This article intends to be an approach to Art Therapies since although they have been developed for many years in other areas of the continent; they are relatively new in our country, as a discipline. We pretend to provide with a historical review, a definition and some theoretical basics sustaining this practice. Finally, we present our proposal in the formation of professionals through the Diploma Course this university has offered since some years ago.